Confirmatory factor analysis of a two scale model of the Health of the Nation Outcome Scales (HoNOS) across diagnostic categories. (January 2017) - Muncer, Steven; Speak, Barry
Abstract: The study examines the fit of a two factor model of the Health of the Nation Outcome scales for a large sample of patients referred to mental health services in England. The fit of the model for different diagnostic groups delineated by the English mental health cluster system is investigated. Overall the fit of the model is excellent at the supercluster level of psychotic disorders, organic disorders and good for non-psychotic disorders. It is, however, not as good at the cluster level. Highlights: A two factor model of HoNOS is tested on a large sample of mental health referrals. Although it is a better model overall than previous models it still has problems. It is not a very good fit to less serious mental health problems and also poor with some psychotic classifications.